DEVELOPING GUIDELINES FOR STUDENT AFFAIRS ADMINISTRATION ACCORDING TO THE DEMING QUALITY CYCLE (PDCA) TOWARDSTHE EXCELLENCE OF SECONDARY SCHOOLS UNDER THE SECONDARY EDUCATIONAL SERVICE AREAOFFICE KALASIN - Saisawang, Wariya; Srisa-ard, Boonchom (Academic Journal of Mahamakut Buddhist University Roi Et Campus, 2023)
The objectives of this research were 1) to study the current condition, the desirable condition, 2) to develop guidelines for student affairs administration according to the Deming Quality Cycle (PDCA) towards the excellence of secondary schools Under the Office of The Secondary Educational Service Area Kalasin. The samples were 325 students under the Secondary Educational Service Area Office Kalasin. 9 experts. The research tools were questionnaires, interview forms, assessment forms. The tools used in the research were. The statistics used to analyze the data were percentage, mean and standard deviation. The analysis of data is an interview form to analyze data by summarizing issues. The results showed that 1. The current state of student affairs administration according to the Deming Quality Cycle (PDCA) of secondary schools under the Secondary Educational Service Area Office Kalasin. The overall level is moderate. The desirable condition of student affairs administration according to the quality cycle Deming (PDCA) of secondary schools under the Secondary Educational Service Area Office Kalasin overall were at the highest level. And when analyzing the need improvement index (PNImodified) of student affairs administration of secondary schools under the Kalasin Secondary Educational Service Area Office, the overall needs were ordered from the most to the least as follows: No. 1 Management Student affairs No. 2 Operation of the student support system and the promotion of democracy in schools. No. 3: promoting and developing students to have discipline, morality, ethics and evaluation of student affairs performance, respectively. 2. The development of the school's student affairs management guidelines according to the Deming Quality Cycle (PDCA) towards excellence in secondary schools under the Secondary Educational Service Area Office Kalasin consists of 6 aspects: student affairs planning; Management of student affairs in promoting and developing students to have discipline, morality, and ethics; in the promotion of democracy in schools and evaluation of student affairs performance. Assessment results The Possibilities of the School's Student Affairs Administrative Development Guidelines According to the Deming Quality Cycle (PDCA) to Secondary School Excellence Under the Secondary Educational Service Area Office Kalasin by the experts found that in terms of suitability, the experts had an opinion that the overall suitability was at the highest level. And in terms of feasibility, the experts had an opinion that overall, it was possible at the highest level that could be used.